Attosecond X-ray spectroscopy reveals the competing stochastic and ballistic dynamics of a bifurcating Jahn-Teller dissociation - Matselyukh, Danylo; Svoboda, Vít; Wörner, Hans Jakob (Nature communications, 2025)
A fundamental approach to understanding chemical processes involves two key concepts: reaction paths and vibrational wavepackets. Collecting sufficient observables to experimentally determine these paths still challenges the latest advances in ultrafast science. Simultaneously observing the coherent nature of the wavepacket following them is even more challenging. Here, exploiting the sub-femtosecond time resolution (σ = 1 fs) of attosecond soft-X-ray-absorption spectroscopy, we overcome both of these challenges and observe a Jahn-Teller-mediated chemical reaction in its entirety-from initial symmetry breaking to beyond dissociation. We find that the Jahn-Teller effect in SiH 4 + immediately bifurcates the reaction into two channels: ballistic dissociation into SiH 3 + and H in 22.9 ± 0.5 fs in which the vibrational wavepacket is preserved, and-after an induction time of 11 ± 3.4 fs-a stochastic dissociation into SiH 2 + and H2 with a timescale of 140 ± 19 fs in which the wavepacket dephases. We find that adiabatic ab-initio molecular dynamics simulations correctly reproduce the ballistic channel, but fail with the stochastic channel. These unprecedented insights into an ultrafast Jahn-Teller-mediated chemical reaction establish the unique potential of our experimental scheme for investigating chemical processes, particularly ones containing non-adiabatic dynamics or involving hydrogen atoms, which are notoriously difficult to detect with other methods, such as electron or X-ray diffraction.